2010
DOI: 10.1007/s10802-010-9439-5
|View full text |Cite
|
Sign up to set email alerts
|

The Dopamine Receptor D4 Gene (DRD4) Moderates Family Environmental Effects on ADHD

Abstract: Attention-Deficit/Hyperactivity Disorder (ADHD) is a prime candidate for exploration of gene-by-environment interaction (i.e., G × E), particularly in relation to dopamine system genes, due to strong evidence that dopamine systems are dysregulated in the disorder. Using a G × E design, we examined whether the DRD4 promoter 120-bp tandem repeat polymorphism, previously associated with ADHD, moderated the effects of inconsistent parenting and marital conflict on ADHD or Oppositional-Defiant Disorder (ODD). Parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
57
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(65 citation statements)
references
References 62 publications
8
57
0
Order By: Relevance
“…The G×E observed for negative parenting was robust for inattention symptoms, supporting previous work that negative parenting adversely affects ADHD dimensions and EB (Martel et al 2010;Pfiffner et al 2005). However, negative parenting is influenced by environmental and genetic factors (Martel et al 2010), including in response to the child's negative behavior (Lytton 1990).…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…The G×E observed for negative parenting was robust for inattention symptoms, supporting previous work that negative parenting adversely affects ADHD dimensions and EB (Martel et al 2010;Pfiffner et al 2005). However, negative parenting is influenced by environmental and genetic factors (Martel et al 2010), including in response to the child's negative behavior (Lytton 1990).…”
Section: Discussionsupporting
confidence: 80%
“…The G×E observed for negative parenting was robust for inattention symptoms, supporting previous work that negative parenting adversely affects ADHD dimensions and EB (Martel et al 2010;Pfiffner et al 2005). However, negative parenting is influenced by environmental and genetic factors (Martel et al 2010), including in response to the child's negative behavior (Lytton 1990). Lee et al (2010) reported that the association of maternal DAT1 genotype and negative parenting was moderated by the child's EB, suggesting that parenting (although conceptualized in this study as an environmental influence) is, itself, also potentially influenced by G×E.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…In the home, for example, negative parenting practices such as harsh or inconsistent discipline have been identified as important risk factors for, as well as outcomes of, disruptive behaviour disorders such as ADHD, conduct disorder and oppositional defiant disorder [15][16][17]. Analogous transactions may occur in the school environment where, for example, relationships with teachers can be affected by but can also shape disruptive behaviour problems [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…COMT has a key role in inactivating dopamine in the prefrontal cortex. Usually, the A1 allele of a 3 0 Taq1 polymorphism in DRD2, the 7-repeat (7r) allele of a 48-bp VNTR polymorphism in exon 3 of DRD4 (for another polymorphism, Martel et al 2011), and the 10-repeat (10r) allele of a 40-bp VNTR polymorphism in DAT are considered as ''risk alleles,'' which may be linked to a less efficient dopaminergic system (Pavlov et al 2012). For COMT, homozygosity for the val allele of the Val158Met polymorphism is frequently regarded as risk genotype.…”
Section: Molecular Genetic Studies Of G Ementioning
confidence: 99%